PERBANDINGAN PERHITUNGAN HARGA POKOK PRODUK MENGGUNAKAN METODE ACTIVITY BASED COSTING DAN METODE KONVENSIONAL DALAM PEMBUATAN BAGLOG JAMUR TIRAM PADA KELOMPOK TANI BORNEO MITRA JAMUR - Putra, Aditya Pratama (EKONOMIA, 2019)
The purpose of this study was to describe and analyze the cost of the products of the growing media of oyster mushroom based on the abc method in the mushroom Borneo farmer group.The basic theory in this study is coast accounting, cost accounting is an activity procedure regarding recording, classifying summarizing and presenting costs and resources used in company operations, cost accounting is also part of management accounting.The analytical tool used in this study is a comparative descriptive analysis method that shows and compares the method of calculating the cost of the product that has been applied so far using the abc method.The result of the calculation of the cost of the product by using the abc method per unit is 5.000 IDR higher than the calculation of the cost of the conventional product method, namely the previous is 4.500 IDR different of 500 IDR unit. This happens because the abc method has allocated real production costs in production. Based on the analysis it can be conchided that this study shows that the calculation of the cost of product using abc is more appropriate, because it proceduces more accurate with higher result comparated to convensional methods, the result of calculations using the abc method will help business owner in making decisions.